2014
DOI: 10.1089/met.2013.0065
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Intake and Cardiometabolic Risk Factors in Adolescents

Abstract: Background: A growing body of research suggests that vitamin D might play an important role in overall health. No data exist on vitamin D intake for the Azorean adolescent population. The purpose of this study was to assess vitamin D intake and investigate a possible association between vitamin D intake and cardiometabolic risk factors in Azorean adolescents. Methods: A cross-sectional school-based study was conducted on 496 adolescents (288 girls) aged 15-18 years from the Azorean Islands, Portugal. Anthropom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The details of more relevant studies that were excluded are demonstrated in supporting information Table S1. Studies were excluded if they: (1) reported correlation coefficient, standard, or unstandard coefficient ( β or B) for MetS prevalence; or reported mean ± SD or mean ± SE or median (interquartile range) of circulating vitamin D levels in those with and without MetS 15,39–41 ; (2) considered MetS as the exposure and serum vitamin D level as the outcome 42,43 ; (3) reported only serum 1,25 (OH)2 D3 levels in both healthy and MetS groups; or assessed the relation of circulating 1,25 (OH)2 D3 and components of MetS 29,44 45 .…”
Section: Methodsmentioning
confidence: 99%
“…The details of more relevant studies that were excluded are demonstrated in supporting information Table S1. Studies were excluded if they: (1) reported correlation coefficient, standard, or unstandard coefficient ( β or B) for MetS prevalence; or reported mean ± SD or mean ± SE or median (interquartile range) of circulating vitamin D levels in those with and without MetS 15,39–41 ; (2) considered MetS as the exposure and serum vitamin D level as the outcome 42,43 ; (3) reported only serum 1,25 (OH)2 D3 levels in both healthy and MetS groups; or assessed the relation of circulating 1,25 (OH)2 D3 and components of MetS 29,44 45 .…”
Section: Methodsmentioning
confidence: 99%
“…So far, the present study has been one of few to evaluate the association between vitamin D intake and lipid profile in children. A study with Portuguese adolescents showed that low vitamin D intake was associated with a worse metabolic profile, including low HDL-C ( 23 ) . In New Zealand, children fed milk fortified with vitamin D had serum concentrations of HDL-C improved ( 40 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies with children and adolescents have shown associations between serum 25(OH)D concentrations and lipid profile markers ( 21 , 22 ) . Nevertheless, the relationship between vitamin D intake and these markers has not been confirmed in the literature, especially in children ( 23 ) .…”
mentioning
confidence: 95%
“…For HDL-c levels, the scores were obtained using the inverse of the formula, considering that it is inversely related to cardiovascular risk. An individual with a Z-score ≥1 SD was at higher risk [34].…”
Section: Cardiometabolic Risk Scorementioning
confidence: 99%